Effects of using a porous disk on the dynamic features of phase change process with PCM integrated circular pipe during nano-liquid forced convection in discharging operation mode - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier, 2021)
Impacts of using a porous disk on the performance of a phase change material filled cylindrical container during forced convection of nanoliquid in discharging mode are investigated with finite element method. Simulations are performed for various values of porous disk permeability (10(-5) <= Da <= 5 x 10(-2)), radius (0 <= p(r)<= h(r)) and height (0:2h(z)<= p(z)<= 0.8h(z)) of the porous disk while time is considered between 0 and 40 min. As the heat transfer fluid, nanoliquid of water containing cylindrical shaped alumina nanoparticle is considered with solid volume fraction of 2%. It was observed that the flow field, temperature and phase change process dynamic features are influenced by varying the porous disk permeability and its geometrical parameters. An optimum permeability value of the disk is observed at Darcy number of 5 x 10(-3) for which the discharging time is minimum and its reduction is 40.7% as compared to case with the lowest permeability of the disk. The phase change process becomes fast with higher radius of the porous disk while the effect is reverse for higher height of the disk. The reduction is discharging time is 22% with highest radius while is it increased by about 61% at the highest height. A predictive model based on feed-forward artificial neural networks is considered with 25 neurons in the hidden layer which delivers accurate results for the effects of porous disk on the dynamic features of phase change process. (C) 2021 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Porous disk; Phase change process; Nanoliquid; Nanofluids; Finite element method; Artificial neural network